Effect of pyridoxine in attenuating pulmonary pyroptosis induced by third-hand smoke exposure: An in silico and in vivo study in male Wistar rats - Astari Pranindya Sari; Reviono Reviono; Agus Dwi Susanto; Dono Indarto (Journal of Advanced Biotechnology and Experimental Therapeutics)
Third-hand smoke (THS) refers to the residual toxic substances that settle on surfaces following the combustion of tobacco. Although concerns about its health implications are increasing, studies exploring its impact on the lungs and potential protective strategies remain scarce. Thus, this study explored the potential of pyridoxine (vitamin B6), known for its anti-inflammatory and antioxidant effects, to alleviate THS-induced pulmonary pyroptosis, using both in silico modelling and in vivo experimentation. Molecular docking was employed to evaluate the binding affinity of pyridoxine to key molecular targets involved in pyroptosis, followed by a 30-day in vivo investigation using 30 male Wistar rats (n = 6 per group). The animals were randomly assigned to five groups: a control group exposed to clean air, and four groups subjected to THS exposure equivalent to 12 cigarettes/day. Of the THS-exposed groups, three received oral pyridoxine (3.5, 7, and 14 mg/kg body weight). On day 30, several parameters were assessed: cotinine levels (blood and urine), pyridoxine concentrations (lung and blood), lung pyroptosis markers (Caspase-1 activity, cleaved Gasdermin D, Interleukin-18), and lung injury indicators (Interleukin-1β levels and histopathological alterations). Docking analysis revealed that pyridoxine engages the same binding site as Ac-FLTD-CMK, a well-characterised Caspase-1 inhibitor. In THS-exposed rats, pyridoxine administration resulted in dose-dependent reduction in Caspase-1 activity, cleaved Gasdermin D, and Interleukin-18 levels, alongside improvements in lung injury scores and associated markers. Collectively, these findings suggest that pyridoxine may confer a protective effect against THS-induced pulmonary pyroptosis. [ J Adv Biotechnol Exp Ther 2025; 8(2.000): 353-369]